FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL LQ45 DI BURSA EFEK INDONESIA - Asoka, Rano (Universitas muhammadiyah palembang, 2016)
This study aims to investigate factors affecting firms’ capital structure listed on Indonesian Stock Exchange. According to sampling formula to determine the sample size, 15 firms are chosen as sample on this study. The data collection tecnique used is primary data. The results reveal that all variables have a significant and positive impact on capital structure. Furthermore, profitability is the main factor affecting firms’ capital structure. Apparently, capital structure only 34,4% can be explained by all dependent variables.